Generational change in pensioner organisations: challenges and opportunities in leadership succession - Stumpf-Tamás; Móré (Magyar Gerontológia, 2025)
Leadership succession is a crucial factor in ensuring the sustainability of organisations across both business and civil sectors, particularly in community-based organisations whose activities are strongly person-dependent and locally embedded.